Fiscal Governance in the Eurozone: How Effectively Does the Stability and Growth Pact Limit Governmental Debt in the Euro Countries?. Issue 2 (4th December 2014) - Koehler, Sebastian; König, Thomas
Abstract : The European sovereign debt crisis continues to hold Europe and the world captive. Will the euro and the fiscal mechanism of the eurozone survive? And how effective is the Stability and Growth Pact (SGP)? Do the euro countries generally fail to comply with the rules of fiscal governance, or does the eurozone need a more member-specific fiscal mechanism? This article examines whether and how the SGP influenced the development of government debt making in the euro countries after the introduction of the common currency. While the SGP could not prevent euro countries from exceeding their deficits, this study's synthetic control analysis reveals that the mechanism has effectively reduced the overall government debt of euro countries since 1999. In particular, donor countries were able to control governmental spending, while many recipient countries—including Greece, Portugal and Italy—have increased government debt ever since, resulting in the European sovereign debt crisis. This suggests that while the SGP effectively constrained overall government debt making, a more sophisticated mechanism is required for safeguarding compliance in large recipient countries.